Controlling w zarządzaniu proekologicznym przedsiębiorstw przemysłowych - Szczypa, Piotr (Controlling in Proecological Management of Industrial Enterprises, 2005)
The aspects of environmental protection are sighted by society more frequently. The managers of industrial enterprises fit also instruments of managements for requirements of this area. Controlling can support the process of proecological management in industrial enterprises to complex manner. The article presents basic questions and the role of controlling in the area of environmental protection concerning industrial enterprises.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 337-342